Maqasid Al Shari’ah as an Instrument for Tackling Women’s and Families Displacement, Insecurity and Criminal Enticement in the North Eastern Nigeria - Saidu Ado; Mohamed A. Salama; Yasser Mohamed Tarshany (QURU’: Journal of Family Law and Culture, 2026)
The prolonged humanitarian crisis in North Eastern Nigeria has intensified the displacement of women and families, increased insecurity, and heightened vulnerability to criminal enticement. Existing responses have largely relied on security and public policy approaches, while the Islamic normative framework remains underutilized. This article aims to examine Maqasid al-Shari’ah as a conceptual and practical instrument for addressing these challenges. Using a qualitative library-based method with a descriptive-analytical approach, the study finds that Maqasid al-Shari’ah can be operationalized through the protection of life, lineage, property, intellect, and religion, manifested in security provision, family reunification, economic assistance, education, prevention of exploitation, and the strengthening of moral values and social solidarity. Thus, Maqasid al-Shari’ah is not only normatively relevant but also provides a foundation for community-based social interventions aimed at protecting victims, strengthening families, preventing crime, and restoring the dignity of vulnerable groups. The study contributes by offering an integrative and applicable maqasid-based framework for addressing displacement, insecurity, and criminal enticement in contemporary conflict settings.